2019
DOI: 10.3390/medicina55100681
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Saccharin Consumption and Increased Risk of Obesity, Diabetes, Hepatic Dysfunction, and Renal Impairment in Rats

Abstract: Background and objectives: This study evaluated the effect of chronic consumption of saccharin on important physiological and biochemical parameters in rats. Materials and Methods: Male Wistar rats were used in this study and were divided into four groups: A control group and three experimental groups (groups 1, 2, and 3) were treated with different doses of saccharin at 2.5, 5, and 10 mg/kg, respectively. Each experimental group received sodium saccharin once per day for 120 days while the control group was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 73 publications
5
29
1
3
Order By: Relevance
“…specifically, one study that used the ADI-dosage for human consumption (15 mg/kg/day) showed no effect on body weight in mice after 8 weeks of acesulfame-K consumption, while another study shows an increase in body weight by exceeding the ADI more than 2-fold (37.5 mg/kg/day) after 4 weeks in mice (85,86). Furthermore, saccharin consumption was found to increase body weight in mice compared to water, sucrose or glucose, whereas other studies in rodents have shown reduced or unchanged body weight compared to mice receiving water, glucose, fructose or sucrose (87)(88)(89)(90)(91)(92)(93)(94). However, the absorption of saccharin is lower in rodents compared to humans due to a relative higher stomach pH in rodents (92).…”
Section: Body Weight and Adipositymentioning
confidence: 92%
See 1 more Smart Citation
“…specifically, one study that used the ADI-dosage for human consumption (15 mg/kg/day) showed no effect on body weight in mice after 8 weeks of acesulfame-K consumption, while another study shows an increase in body weight by exceeding the ADI more than 2-fold (37.5 mg/kg/day) after 4 weeks in mice (85,86). Furthermore, saccharin consumption was found to increase body weight in mice compared to water, sucrose or glucose, whereas other studies in rodents have shown reduced or unchanged body weight compared to mice receiving water, glucose, fructose or sucrose (87)(88)(89)(90)(91)(92)(93)(94). However, the absorption of saccharin is lower in rodents compared to humans due to a relative higher stomach pH in rodents (92).…”
Section: Body Weight and Adipositymentioning
confidence: 92%
“…Furthermore, saccharin consumption was found to increase body weight in mice compared to water, sucrose or glucose, whereas other studies in rodents have shown reduced or unchanged body weight compared to mice receiving water, glucose, fructose or sucrose ( 87 94 ). However, the absorption of saccharin is lower in rodents compared to humans due to a relative higher stomach pH in rodents ( 92 ). Furthermore, differences in perception of sweetness for individual artificial sweeteners exist between different rodent species and strains ( 95 ).…”
Section: Pharmacokineticsmentioning
confidence: 99%
“…An increased body weight was noted in rats after 60 and 120 days of 5 mg/kg saccharin treatment. Authors also observed an increase in glucose, uric acid and creatinine levels, as well as in oxidative status in the liver of saccharin-treated rats, suggesting that saccharin may impair glucose homeostasis, induce obesity and lead to impairments in kidney and liver function (140). The World Health Organization and the EU Scientific Committee for Food declared saccharine as safe up to the approved daily intake doses (5 mg/kg body weight) (53).…”
Section: Saccharin (E-954)mentioning
confidence: 98%
“…However, very high saccharin concentrations were tested in animal models, if compared to the doses commonly ingested by humans (139). With regard to metabolic parameters, a recent study evaluated the administration of saccharin (at different doses, namely: 2.5, 5, and 10 mg/kg) in male Wistar rats (140). An increased body weight was noted in rats after 60 and 120 days of 5 mg/kg saccharin treatment.…”
Section: Saccharin (E-954)mentioning
confidence: 99%
“…Chi et al [8] reported neotame effect on the gut microbiome, and it concluded that neotame induces adverse effects on gut microbiota. The risk of obesity and diabetes also increased due to long-term saccharin consumption [9]. Some regulatory authorities deal with food control around the globe, such as Joint FAO/WHO Expert Committee on Food Additives (JECFA), Codex Alimentarius Commission (CAC), Food and Drug Administration (FDA) from the United States, Food Standards Australia New Zealand (FSANZ), and National Agency of Drug and Food Control (NADFC) of the Republic of Indonesia have determined the Acceptable Daily Intake (ADI) value and maximum amount for high-intensity sweeteners in foodstuffs (Table 1).…”
Section: Use Of Sweeteners In Foodstuffs and The Regulationsmentioning
confidence: 99%